1995
DOI: 10.1136/gut.37.3.305
|View full text |Cite
|
Sign up to set email alerts
|

Heartburn in patients with achalasia.

Abstract: (Gut 1995; 37: 305-308)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 12 publications
2
53
0
3
Order By: Relevance
“…Heartburn occurs frequently in achalasia. Patients with heartburn have lower LES pressures than those without this symptom [19] . Heartburn may occur as a result of gastro-esophageal reflux or other causes, such as direct irritation of the esophageal mucosa by foods, pills, and the lactate produced by bacterial fermentation of retained carbohydrates [19,20] .…”
Section: Clinical Featuresmentioning
confidence: 91%
See 1 more Smart Citation
“…Heartburn occurs frequently in achalasia. Patients with heartburn have lower LES pressures than those without this symptom [19] . Heartburn may occur as a result of gastro-esophageal reflux or other causes, such as direct irritation of the esophageal mucosa by foods, pills, and the lactate produced by bacterial fermentation of retained carbohydrates [19,20] .…”
Section: Clinical Featuresmentioning
confidence: 91%
“…Patients with heartburn have lower LES pressures than those without this symptom [19] . Heartburn may occur as a result of gastro-esophageal reflux or other causes, such as direct irritation of the esophageal mucosa by foods, pills, and the lactate produced by bacterial fermentation of retained carbohydrates [19,20] . Hiccup is also a frequent symptom in achalasia, partly because of the obstruction of the distal esophagus [21] .…”
Section: Clinical Featuresmentioning
confidence: 91%
“…19,20 However, whether the low esophageal pH in these patients is caused by retention of lactic acid from bacterial fermentation of retained food or true refluxed gastric acid is controversial. Spechler et al 10 showed that patients who have achalasia with heartburn have lower basal LES pressure than patients without heartburn. Because GERD and achalasia are 2 coincidental diseases, patients with heartburn have lower basal LES pressure due to GERD.…”
Section: Are Gastroesophageal Reflux Disease and Achalasia Coincidentmentioning
confidence: 99%
“…10,17,21,22 Conversely, patients with achalasia are insensitive to acid in the esophagus. 23 Fisichella et al 8 reported data from 145 untreated achalasia patients.…”
Section: Does Reflux Occur In Achalasia?mentioning
confidence: 99%
See 1 more Smart Citation